Soul Sports Physio and Rehab Booking Management System - CHEE, SENG YIK; SULAIMAN, RABATUL ADUNI (Applied Information Technology And Computer Science, 2025)
Sports rehabilitation centers like Soul Sports Physio face operational inefficiencies from manual appointment, attendance, and data management, leading to scheduling conflicts and poor client experiences. This project addressed these by designing, developing, and testing the Soul Sports Physio and Rehab Booking Management System (SPRBMS). Designed with an object-oriented approach, SPRBMS is a cross-platform Flutter mobile app for clients and trainers and a web admin panel, using a Node.js backend and MongoDB database. Key features include QR-code session verification, real-time notifications, and payment processing. Functional and User Acceptance Testing confirmed SPRBMS streamlines bookings, improves data management, and offers a user-friendly interface, proving a viable digital transformation solution for physiotherapy services.